THE IMPACT OF YOUTUBE CONTENT ON CHILD PSYCHOLOGY: A COMPREHENSIVE STUDY - Idyan, Zamna (Lafadz Jaya Publisher, 2025)
The increasing consumption of digital media, particularly YouTube, among children has raised concerns about its potential effects on their psychological development. This study explores the relationship between children's YouTube viewing habits and various psychological outcomes. The research is guided by the need to understand how exposure to certain types of content influences cognitive, emotional, and behavioral development. Data was gathered through a mixed-method approach, combining surveys of children's viewing preferences with psychological assessments. Findings indicate a significant correlation between exposure to specific content, such as educational videos and entertainment channels, and children’s attention span, emotional regulation, and social behaviors. The study also identifies possible risks associated with excessive screen time, including negative impacts on self-esteem and social skills. This paper offers critical insights into the importance of parental guidance and media literacy in managing children's YouTube consumption, providing recommendations for future research and policy development in media regulation.